2011
DOI: 10.1063/1.3596444
|View full text |Cite
|
Sign up to set email alerts
|

Current-limiting behavior in multijunction solar cells

Abstract: Experimental measurements on tandem GaInAsP/InGaAs concentrator solar cells are presented that demonstrate how the short-circuit current can shift from that of the higher current subcell to that of the lower current subcell as irradiance increases. Theoretical modeling illustrates how this can occur when the current-limiting subcell has a noticeably nonzero slope in its current-voltage curve near short-circuit, and should be general to all series-connected multijunction cells of this nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…This is attributed to the non-zero slope photocurrent of the dilute nitride subcell both at near short circuit conditions and in reverse bias (between -2.5V and 0V) as a result of the electric-field assisted collection which is dependent on voltage. Similar trends have been already reported for a GaInAsP/InGaAs dual-junction solar cell [13]. Therefore, it can be concluded that the electric field-assisted increase of the carrier collection and Jsc is not useful to increase the efficiency of this subcell.…”
Section: Modeling the Performance Of 4-junction Solar Cellssupporting
confidence: 67%
“…This is attributed to the non-zero slope photocurrent of the dilute nitride subcell both at near short circuit conditions and in reverse bias (between -2.5V and 0V) as a result of the electric-field assisted collection which is dependent on voltage. Similar trends have been already reported for a GaInAsP/InGaAs dual-junction solar cell [13]. Therefore, it can be concluded that the electric field-assisted increase of the carrier collection and Jsc is not useful to increase the efficiency of this subcell.…”
Section: Modeling the Performance Of 4-junction Solar Cellssupporting
confidence: 67%
“…In that situation, the current density from the tandem should be larger or equal to the smallest one from the two subcells. 4,19 In the present configuration, the small-molecule subcell has lower J sc ¼ 3.94 mA/cm 2 than the polymer cell J sc ¼ 6.38 mA/ cm 2 . However, the tandem cell delivers J sc ¼ 2.78 mA/cm 2 , which is only 70% of the limiting cell current, meanwhile the fill factor of the tandem is 45%, which is quite close to the 47% of the limiting cell.…”
mentioning
confidence: 65%
“…A supplemental, suitably filtered, illumination source (test lamp) is added to the setup, with an emission spectrum strictly matched to the absorption range of the top subcell. When the intensity of the supplemental illumination is increased, if the multijunction sample cell is top limited, its J sc short‐circuit current will increase until the value of the current produced by the middle subcell, a point we call the “current match.” If this supplemental illumination is further raised, the sample will become middle limited: The measured new J sc will coincide with the current of middle subcell (with excellent approximation). Therefore, the trend of the short‐circuit current as a function of the supplemental illumination given by the test lamp provides information about the limiting subcell together with an estimation of the effective limiting current.…”
Section: Principles Of the Techniquementioning
confidence: 99%
“…A supplemental, suitably filtered, illumination source (test lamp) is added to the setup, with an emission spectrum strictly matched to the absorption range of the top subcell. When the intensity of the supplemental illumination is increased, if the multijunction sample cell is top limited, its J sc short-circuit current will increase 28 until the value of the current produced by the middle subcell, a point we call the "current match." If this supplemental illumination is further raised, the sample will become…”
Section: Principles Of the Techniquementioning
confidence: 99%